Phenolic profile of dark-grown and photoperiod-exposed Hypericum perforatum L. Hairy root cultures - Tusevski, Oliver; Petreska Stanoeva, Jasmina; Stefova, Marina; Simic, Sonja Gadzovska (Hindawi Limited, 2013)
Hypericum perforatum L. is a medicinal plant considered as an important natural source of secondary metabolites with a wide range of pharmacological attributes. Hairy roots (HR) were induced from root segments of in vitro grown seedlings from H. perforatum after cocultivation with Agrobacterium rhizogenes A4. Investigations have been made to study the production of phenolic compounds in dark-grown (HR1) and photoperiod-exposed (HR2) cultures. The chromatographic analysis of phenolic acids, flavonols, flavan-3-ols, and xanthones revealed marked differences between HR1 and HR2 cultures. The production of quinic acid, kaempferol, and seven identified xanthones was increased in HR2. Moreover, HR2 showed a capability for de novo biosynthesis of two phenolic acids (3-p-coumaroylquinic acid and 3-feruloylquinic acid), three flavonol glycosides (kaempferol hexoside, hyperoside, and quercetin acetylglycoside), and five xanthones (tetrahydroxy-one-methoxyxanthone, 1,3,5-trihydroxy-6-methoxyxanthone, 1,3,5,6-tetrahydroxy-2-prenylxanthone, paxanthone, and banaxanthone E). On the other side, HR1 cultures were better producers of flavan-3-ols (catechin, epicatechin, and proanthocyanidin dimers) than HR2. This is the first comparative study on phenolic profile of H. perforatum HR cultures grown under dark and photoperiod conditions.